Working memory capacity as a moderator of load-related frontal midline theta variability in Sternberg task - Zakrzewska, Marta Z.; Brzezicka, Aneta (Frontiers in Human Neuroscience, 2014)
The aim of this study was to investigate the relationship between working memory capacity (WMC) and frontal theta response to memory load in Sternberg task. We show that oscillatory activity in the theta band (4 – 6 Hz) related to Sternberg task performance may differentiate people characterized by high and low WMC. Specifically, there is a linear increase of frontal midline (FM) theta power with load, however only in the high working memory capacity group. Furthermore, a positive linear relationship was found between WMC (OSPAN score) and average FM theta power increase from lower to higher loads which was not present at other scalp locations. The distinct patterns of high and low WMC individual’s FM theta response to memory load seem to support the assumption that theta activity during maintenance reflects not only the amount of information stored, but also the effort it takes to remember them and the efficiency of involved neural processes. This contributes to perceiving FM theta as an individual trait which can reflect individual working memory mechanism efficiency.